Physiological characteristics of elite snowboarders - Vernillo, G.; Pisoni, C.; Thiebat, G. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The aim of this study was to profile the physiological qualities of elite snowboarders and quantified the relationships with snowboarding performance.